Chandrabala Modi Academy, Ankleshwar (A) - Dixit, Mukund R.; Sharma, Rajeev (Of Indian Institute of Management, Ahmedabad) (London : Indian Institute of Management, Ahmedabad, 2006)
The case is intended to teach students about leadership and the role of a leader as an innovator. The case describes a new school, the Chandrabala Modi Academy, which has the opportunity to take part in an innovative event: crossing the river Narmada as a campaign against the use of drugs. The event has great potential benefits in building the name of the school but any failure would be catastrophic for the fledgling school. Students are then invited to make a decision as to what they would do in place of the principal Mr Bhattacharya.
Originally published in Dixit, M., & Sharma, R. (2006). Chandrabala Modi Academy, Ankleshwar (A). RJMC0002(A). Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Chandrabala Modi Academy; Business planning; Strategic planning; Decision making; Industrial management